SOSIOLOGI DIGITAL: SUATU PARADIGMA BARU DALAM KAJIAN ILMU SOSIAL - T Tendi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2016)
AbstractThis article is a description or an overview about the development of digital sociology as part of a contemporary sociology studies. In order to make the article more firmly, the author have searched a lot of data and conducted a study of literature. The world kept turning and growing very fast, if social science studies do not well developed to match the moves, then it will will inevitably be left behind and knowledge is no longer relevant. Therefore, new knowledge contextually relevant to the times become an extremely important point to note. Digital sociology which in recent years have become the talk of the world scholars is one of the new paradigm that needs to be explored by practitioners and social scientists. The contemporary context which is offered by digital sociology is a response to the development of technology and a new life space or called as the cyberspace, which is attracting many people from the real world to be involved in it.AbstrakArtikel ini adalah sebuah deskripsi yang merupakan gambaran mengenai perkembangan sosiologi digital sebagai bagian dari kajian sosiologi kontemporer. Agar tulisan ini lebih ber-nash, maka penulis banyak mencari data dengan melakukan kajian kepustakaan. Dunia ini terus berputar dan berkembang dengan sangat cepat, jika kajian ilmu sosial tidak turut pula dikembangkan untuk menyamai gerak perubahan itu maka pasti akan tertinggal dan pengetahuannya tidak lagi relevan. Karena itu, pengetahuan baru yang konteksnya sesuai dengan zaman menjadi suatu hal yang amat penting untuk diketahui. Sosiologi digital yang beberapa tahun belakangan ini menjadi perbincangan para akademisi dunia merupakan salah satu paradigma baru yang perlu didalami oleh para praktisi dan ilmuwan sosial. Konteks kekinian yang ditawarkan sosiologi digital merupakan jawaban atas berkembangnya teknologi dan suatu ruang kehidupan baru bernama dunia maya yang telah melibatkan banyak orang dari dunia nyata untuk berkecimpung di dalamnya.Pengutipan: Tendi. (2016). Sosiologi Digital: Suatu Paradigma Baru dalam Kajian Ilmu Sosial . SOSIO DIDAKTIKA: Social Science Education Journal, 3(2), 2016, 135-146. doi:10.15408/sd.v3i2.5055.Permalink/DOI: http://dx.doi.org/10.15408/sd.v3i2.5055